Relationship Between Family Support and Colorectal Cancer Patients' Motivation for Undergoing Chemotherapy - Dedi Irawandi; Setiadi Setiadi; Dwi Priyantini (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Globally, colorectal cancer is one of the most highly prevalent cancers according to the World Health Organization, with the majority of patients undergoing chemotherapy. Various studies show that more than 70% of patients experience significant physiological impacts such as fatigue, nausea, and disruption of daily activities, while approximately 30% experience psychological disorders such as anxiety and depression. Furthermore, more than 60% of patients require family support during treatment. This demonstrates that the impact of chemotherapy is multidimensional, encompassing physical, psychological, and social aspects, necessitating a comprehensive care approach that includes family involvement. The purpose of this study was to determine the relationship between family support and motivation of colorectal cancer patients undergoing chemotherapy. The study design used an observational analytic design with a cross-sectional approach. The study population comprised all 55 colorectal cancer patients undergoing chemotherapy in the Rosella 2 Room at Dr. Soetomo Hospital, Surabaya. A sample of 48 people was taken using the Simple Random Sampling technique. Data analysis used the Spearman Rho correlation test. The results showed that of the 48 respondents, 43 had high family support and 42 had strong motivation. Bivariate analysis showed a significant relationship between family support and patient motivation to undergo chemotherapy. The results of the Spearman Rho test showed a rho value of 0.902 and a significance value of P = 0.000 (< 0.05). The active role of nurses in providing education to families and patients is very important in providing information related to chemotherapy. So that it can provide a sense of security, comfort, and trust in nurses. Thus, patients have strong motivation, high life expectancy, and increased family enthusiasm in accompanying the treatment process.